Do baseball players with soft tissue GIRD have a thicker posterior capsule? - Thomas, S. J.; Sheridan, S.; Reuther, K. E. (Journal of Athletic Training, 2019)
Context: Baseball players often present with clinical Glenohumeral Internal Rotation Defi cits (GIRD). Clinical GIRD is thought to include tissue specifi c adaptations, including humeral retroversion (HR), posterior rotator cuff tightness, and increased posterior capsule thickness (PCT). It has been suggested that correcting clinical GIRD with the amount of HR (soft tissue GIRD) will determine if soft tissue deficits are present. However, it is unknown if glenohumeral posterior capsule contributes to these soft tissue adaptations. Therefore, the purpose of this study was to determine if baseball players with soft tissue GIRD have a thicker posterior capsule compared to those without soft tissue GIRD. Methods: A single group posttest only study design was used, which was performed in a clinical setting. Fifty collegiate and professional baseball players with no current injury or surgery in the past six months were divided into soft tissue GIRD (n = 22, age = 20.9± 2.7 years, mass = 93.5± 8.2 kg, height = 187.9± 5.4 cm) and no soft tissue GIRD (n = 28, age = 21.8± 3.5 years, mass = 93.3± 8.7 kg, height = 190.0± 5.2 cm) groups. Glenohumeral internal rotation (IR) was measured bilaterally with a Saunders Digital Inclinometer (The Saunders Group Inc. Chaska, MN). Patients were positioned supine with the scapula stabilized. Clinical GIRD was then calculated as the bilateral difference in IR (Table 1). HR and PCT was measured with an ultrasound system (Sonosite Titan, Sonosite Inc., Bothell, WA). HR was measured supine with the arm abducted to 90° and elbow fl exed to 90°. PCT was measured seated with the arm at the side in neutral rotation. All methods have previously established excellent reliability. Groups were determined if soft tissue GIRD was present or absent following HR correction (clinical GIRD + HR bilateral difference). Independent sample t-tests were performed to compare dominant arm, non-dominant arm, and the bilateral difference in PCT between the GIRD and no GIRD groups. Results: The GIRD group had no signifi cant differences for dominant (GIRD = 2.91mm, no GIRD= 2.78mm, p=0.9) and non-dominant PCT (GIRD = 2.2mm, no GIRD= 2.19mm, p=0.9), but signifi cantly more PCT bilateral difference compared to the no GIRD (GIRD = 0.36mm, no GIRD= 0.06mm, p=0.0001) group. Conclusions: Healthy baseball players often present with alterations in clinical ROM. It has been well documented that HR contributes to this alteration in ROM, however evidence for soft tissue adaptations is limited. This study found that the bilateral difference in PCT was greater in the group with soft tissue GIRD. It is important for clinicians to know that the bilateral difference in PCT is an important metric to calculate. In addition, knowledge of specifi c tissue adaptations will help guide optimal treatment strategies.